Pengembangan Soal Literasi Numerasi Konteks Budaya Bangka Bagi Siswa SD - Rachma Kurniasi, Eka; Hevitria, Hevitria; Fauziani, Meilidya; Safitri, Indri (Universitas Nusantara PGRI Kediri, 2023)
Literacy and numeracy are important skills of the 21st century. Problems at the elementary level regarding numeracy still need to be developed. This development concerns numeration content and the context of regional culture that need to be included in the questions. This study aims to develop numeracy literacy questions in the cultural context of Bangka Belitung for elementary school students. The research method chosen is development research with the ADDIE development model. The procedure carried out in the Analysis stage is analyzing the SK and KD of fourth grade elementary school in mathematics, analyzing student needs, analyzing the needs of numeracy literacy questions in the 2013 curriculum and the independent curriculum. In the design phase, the researcher made a prototype of numeracy literacy questions in the cultural context of Bangka Belitung. The development stage is validated by material experts and evaluation experts regarding the questions that have been developed. The implementation phase was carried out by small-scale and large-scale tests on the subject of 4th grade elementary school students. The evaluation stage is carried out formative evaluation at each stage of development. The results of the study were 5 questions of numeracy literacy in the cultural context of Bangka Belitung with media expert validation of 87% stating it was valid, evaluation expert validation stating 92% valid. On a small scale, 79% of student responses stated that it was feasible and on a large scale, 82% stated that it was feasible. Test the quality of the items, namely construct validity, it is stated that all items are valid. While reliability is stated as a matter of reliability. This study gives the result that students have difficulty in understanding their literacy. However, on numeracy content, students find it not difficult to do it. When reading the questions students feel proud that some places or foods they know and encounter everyday can be studied in mathematics.